TRAÇOS DE PERSONALIDADE, ESTRESSE, ANSIEDADE, DEPRESSÃO, APEGO E VÍNCULO MÃE-BEBÊ NO CICLO GRAVÍDICO-PUERPERAL - PROCÓPIO, CAMILA VIANA DE ALMEIDA (2019)
The Pregnancy-Puerperal Cycle (CGP) brings sudden changes that require rapid adaptations. The main objective of this research was to evaluate and describe traits of personality, anxiety, depression, stress and mother-baby bond in women in CGP. Sixty-six women from gestation to postpartum participated in this study. Data was through the Google Forms platform. The research was carried out in three stages. In the first stage, the women were at 24 weeks of gestation or more, in the second stage they were in the puerperium (30 days after giving birth) and in the third stage 4 months after giving birth. The following instruments were applied: socio-demographic and health questionnaire; Maternal Fetal Attachment Scale - AMF; Adult Binding Scale - EVA; Perceived Stress Scale - PSS; Self-Report Questionnaire - SRQ-20; Population Screening Scale for Depression (CES-D); Trait-State Anxiety Inventory - IDATE; Personality Inventory - NEO-FFI-R. Maternal Linkage Perception Inventory - IPVM; SPSS was used to analyze the data. Participants were divided into two groups, Experimental Group (EG) with high levels for personality trait neuroticism and Control Group (CG) for participants with low levels of neuroticism. The main results showed that the participants of the CG presented anxiety, both in trait and in state, higher than the participants of the EG. Women with elevated neuroticism express more presence of depression, perceived stress, and common mental disorders. It can be concluded that women with high and very high neuroticism presented more wear and tear, more suffering, presence of depression, high perception of stress, presence of common mental disorder and anxious bond, indicating that they are more reactive. However, these findings did not influence the formation of the mother-baby bond.